Helicobacter pylori coinfection is a confounder, modulating mucosal inflammation in oral submucous fibrosis - Rajendran R; Rajeev R; Anil S; Alasqah Mohammed; Rabi Abdul (Wolters Kluwer Medknow Publications, 2009)
The oral cavity has been considered a potential reservoir for Helicobacter pylori (H pylori) , from where the organism causes recurrent gastric infections. Aim: With this case-control study we tried to evaluate the role of H pylori in the etiology of mucosal inflammation, a condition that compounds the morbid state associated with oral submucous fibrosis (OSF). Materials and Methods : Subjects ( n = 150) were selected following institutional regulations on sample collection and grouped into test cases and positive and negative controls based on the presence of mucosal fibrosis and inflammation. The negative controls had none of the clinical signs. All patients underwent an oral examination as well as tests to assess oral hygiene/periodontal disease status; a rapid urease test (RUT) of plaque samples was also done to estimate the H pylori bacterial load. We used univariate and mutivariate logistic regression for statistical analysis of the data and calculated the odds ratios to assess the risk posed by the different variables. Results : The RUT results differed significantly between the groups, reflecting the variations in the bacterial loads in each category. The test was positive in 52% in the positive controls (where nonspecific inflammation of oral mucosa was seen unassociated with fibrosis), in 46% of the test cases, and in 18% of the negative controls (healthy volunteers) (χ2 = 13.887; P < 0.01). A positive correlation was seen between the oral hygiene/periodontal disease indices and RUT reactivity in all the three groups. Conclusions: The contribution of the H pylori in dental plaque to mucosal inflammation and periodontal disease was significant. Logistic regression analysis showed gastrointestinal disease and poor oral hygiene as being the greatest risk factors for bacterial colonization, irrespective of the subject groups. A positive correlation exists between RUT reactivity and the frequency of mucosal inflammation.